Anisotropic Raman‐Enhancement Effect on Single‐Walled Carbon Nanotube Arrays. Issue 3 (1st December 2017) - Wu, Juanxia; Zhang, Shuchen; Lin, Dewu; Ma, Bangjun; Yang, Liangwei; Zhang, Shuqing; Kang, Lixing; Mao, Nannan; Zhang, Na; Tong, Lianming; Zhang, Jin
Abstract: The charge transfer between molecules and materials can modulate the polarizability tensor of the molecules and lead to an enhancement of the Raman scattering. Surface‐enhanced Raman scattering on in‐plane anisotropic layered materials has suggested the crystalline‐axis‐dependent charge interactions between molecules and materials. However, the full understanding of the anisotropic charge transfer process is still lacking. The rigorous anisotropic nature and structural diversity of single‐walled carbon nanotube (SWNT) provide an ideal platform to systematically study the anisotropic charge transfer process. The present work reports the anisotropic Raman enhancement effect of molecules on horizontally aligned SWNT arrays and attribute it to the charge transfer efficiency that depends on the laser polarization direction and the resonance of SWNTs. The Raman signal of probe molecules on SWNT arrays is enhanced and reaches the maximum intensity when the incident laser is polarized along the SWNT axial direction, and the intensity is the minimum if they are perpendicular to each other. The different efficiencies of charge transfer are further confirmed by polarized optical absorption measurements and the energy alignment analysis. The present work provides a sensitive way to study the tunable charge interactions between molecules and anisotropic low‐dimensional materials, which are also important for polarization‐controlled optoelectronic applications. Abstract : Anisotropic surface‐enhanced Raman scattering on single‐walled carbon nanotube (SWNT) arrays: The rigorous anisotropic structure and electronic structure of SWNT lead to the anisotropic charge interaction between SWNT and probe molecules, resulting in the anisotropic Raman enhancement, that is, Raman enhancement factor of molecules on SWNT arrays depends on the relative angle between laser polarization direction ( e i ) and SWNT axial direction.